Appetite Suppression and Antiobesity Effect of a Botanical Composition Composed of Morus alba, Yerba mate, and Magnolia officinalis - Mesfin Yimam; Ping Jiao; Mei Hong; Lidia Brownell; Young-Chul Lee; Eu-Jin Hyun; Hyun-Jin Kim; Tae-Woo Kim; Jeong-Bum Nam; Mi-Ran Kim; Qi Jia (Journal of Obesity)
Background. Obesity and its comorbidities continue to challenge the world at an alarming rate. Although the long term solution lies on lifestyle changes in the form of dieting and exercising, drug, medical food, or dietary supplement interventions are required for those who are already obese. Here we describe a standardized blend composed of extracts from three medicinal plants: Morus alba, Yerba mate, and Magnolia officinalis for appetite suppression and metabolic disorders management. Method. Extracts were standardized to yield a composition designated as UP601. Appetite suppression activity was tested in acute feed intake rat model. Efficacy was evaluated in C57BL/6J mouse models treated with oral doses of 1.3 g/kg/day for 7 weeks. Orlistat at 40 mg/kg/day was used as a positive control. Body compositions of mice were assessed using a dual energy X-ray absorptiometry (DEXA). ELISA was done for insulin, leptin, and ghrelin level quantitation. Nonalcoholic steatohepatitis (NASH) scoring was conducted. Results. Marked acute hypophagia with 81.8, 75.3, 43.9, and 30.9% reductions in food intake at 2, 4, 6, and 24 hours were observed for UP601. Decreases in body weight gain (21.5% compared to the HFD at weeks 7 and 8.2% compared to baseline) and calorie intake (40.5% for the first week) were observed. 75.9% and 46.8% reductions in insulin and leptin, respectively, 4.2-fold increase in ghrelin level, and reductions of 18.6% in cholesterol and 59% in low-density lipoprotein were documented. A percentage body fat of 18.9%, 47.8%, 46.1%, and 30.4% was found for mice treated with normal control, HFD, Orlistat, and UP601, respectively. 59.3% less mesenteric fat pad and improved NASH scores were observed for UP601. Conclusion. UP601, a standardized botanical composition from Morus alba, Yerba mate, and Magnolia officinalis could be used as a natural alternative for appetite suppression, maintaining healthy body weight and metabolism management.